1990
DOI: 10.1111/j.1365-2125.1990.tb03625.x
|View full text |Cite
|
Sign up to set email alerts
|

A novel method for culturing sweat gland epithelia: comparison of normal and cystic fibrosis tissues.

Abstract: A new method is described to produce epithelial sheets by direct explantation of human sweat glands onto matrigel‐coated millipore filters. The method is applicable to whole glands, separated coils or ducts and to normal and CF tissues. Electrogenic transport studies show that epithelia develop sodium transporting capability, even when explants are derived from secretory coils.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…It is unknown why coil cells differentiate and acquire duct cell characteristics during culture, and vice versa. However, our findings are in agreement with previous reports that primary coil and duct cultures growing on permeable supports reacted similarly to carbachol and isoprenaline stimulation (Brayden & Cuthbert, 1990;Brayden et al, 1991). On the other hand, when the cells were cultured on an impermeable substrate, cultured duct cells were insensitive to methacholine and isoproterenol (Jones et al, 1988).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…It is unknown why coil cells differentiate and acquire duct cell characteristics during culture, and vice versa. However, our findings are in agreement with previous reports that primary coil and duct cultures growing on permeable supports reacted similarly to carbachol and isoprenaline stimulation (Brayden & Cuthbert, 1990;Brayden et al, 1991). On the other hand, when the cells were cultured on an impermeable substrate, cultured duct cells were insensitive to methacholine and isoproterenol (Jones et al, 1988).…”
Section: Discussionsupporting
confidence: 93%
“…This may indicate that in the primary culture, specific characteristics of coil cells are being lost, at least in part of the cell population . One possible explanation for the cAMP effect is that during culture, some coil cells differentiate and acquire characteristics of duct cells (Brayden et al, 1988(Brayden et al, , 1991.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lee et al developed a repeated shearing method that allowed the rapid isolation of intact viable human sweat glands from skin samples, in which it was possible to easily distinguish and separate coil and ductal portions of the human gland to examine individual functions of those regions separately . Explanting glands, coils or ducts in tissue culture, including permeable supports, generated experimental material that allowed the investigation of normal and CF glands using electrophysiology and biochemical techniques . These experiments further revealed that cholinergic and adrenergic agonists could induce transmonolayer anion fluxes expected from secretory cells, suggesting that the cultured monolayer presented a model for understanding the cellular physiology of the intact secretory coil.…”
Section: Cell Culturementioning
confidence: 99%
“…These experiments further revealed that cholinergic and adrenergic agonists could induce transmonolayer anion fluxes expected from secretory cells, suggesting that the cultured monolayer presented a model for understanding the cellular physiology of the intact secretory coil. For a short period, primary culture of human sweat gland cells was used for investigations, instead of animal tissues …”
Section: Cell Culturementioning
confidence: 99%